Lightweight Steel Roof Truss Training for Youth Construction Workers in Padang - Mediana Desfita; Kharisma Permata Sari; Akbar Alfa (Majalah Ilmiah UPI YPTK, 2026)
Lightweight steel roof truss technology is increasingly used in building construction because it is efficient, light, and adaptable to field installation. However, youth construction workers in community-based working groups still face limited technical knowledge, installation experience, and access to specific tools. This community engagement program aimed to improve the competency of the Youth Working Group of Simpang Anduring, Kuranji District, Padang City, in applying proper lightweight steel roof truss installation practices. The activity was implemented through initial survey, preparation, technical socialization, material and equipment introduction, direct field practice, mentoring, and evaluation. The program was conducted on 10-12 October 2025 and involved 20 construction workers. The training covered C75.75 lip-channel profiles, battens, screws, dynabolts, cutting tools, hand drills, measuring tools, and field assembly of trusses and battens. The results showed that participants became more familiar with lightweight steel components, installation sequences, equipment use, and practical work procedures. The program also facilitated tools that can be used by the partner group for future jobs. This activity strengthened technical capacity, improved worker confidence, and created an opportunity for sustainable construction-based income generation in the local youth community.